How different are we? Globalisation and the perceptions of leadership challenges in England and Hong Kong - Mike Bottery (Educational Futures)
This article argues that one of the effects of a globalisation of difference forces is upon the conceptualisation and functioning of education. One of the ways of examining such transformations is to ask educational leaders if they feel that the challenges they are having to deal with are changing, and in what ways. This article then does four things. First, it provides definitions of leadership and culture before describing a number of globalising forces which are having significant effects upon educational systems. Second, it reviews empirical research being conducted in and Hong Kong on the challenges that School Principals believe affect them at the present time and argues that this globalising background provides part of the reason for these Principals’ perceptions of their challenges. Third, it provides conceptual and practical links between these globalising tendencies and Principals’ practice. Finally it argues that these forces may well be having a ‘flattening’ tendency, leading to a reduced influence of cultural factors on leadership challenges.